# Simplify the following expression.a + 2c – 5b – c + a – b?

0

2a – 6b + 2c

2a – 6b + c

a – 6b + c

a – 5b + 2c

• a + 2c – 5b – c + a – b

= a + a – 5b – b + 2c – c

= 2a – 6b + c

:o)

• it quite is fairly common. combine like words. First count sort each and all the numerous variables. that’s 3 diverse ones. 2 a’s, 2c’s. and 2b’s. a + 2c – 5b – c + a – b. a + a = 2a (while there is no sort in front of the letter, the type is a million.) – 5b – b = – 6b (while there is two destructive words, you combine them and use the sign.) 2c – c = c (it quite is like popular subtraction, 2-a million = a million) Your answer is 2a – 6b + c

• To simplify the expression you need to add/subtract all of the like terms (a’s with a’s, b’s with b’s, etc.)

A+2C-5B-C+A-B

It helps if you underline all of the like terms, starting with the first one. Underline all of the A’s once, all of the C’s twice, and all of the B’s three times (this can work with any variable or numbers, not just A, B, or C).

A+A=2A

2C-C=C

-5B-B=-6B

2A+C-6B

• group the a b and c numbers together using whatever signs are in front of them

a+a 2a

-5b-b -6b

+2c-c c

2a-6b+c

Also Check This  Is menudo good for a cold? 